Biomaterials mediated 3R (remove-remodel-repair) strategy: holistic management of Helicobacter pylori infection - Tinglin Zhang; Yating Zheng; Tielou Chen; Yuankai Gu; Yingli Gong; Dewei Wang; Zhaoshen Li; Yiqi Du; Li Zhang; Jie Gao (Journal of Nanobiotechnology)
Abstract Helicobacter pylori (HP) is a major etiological agent of gastric cancer, with a global prevalence of around 50%. Current treatments, primarily based on antibiotics, face challenges such as increasing drug resistance and disruption of the gut microbiota. This review proposes a holistic integrative medicine (HIM) approach, guided by the 3R concept (Remove, Remodel, and Repair), to address these limitations. The 3R concept offers a novel paradigm for the integrated prevention and treatment of HP infections: Remove targets the direct eradication of HP by overcoming antibiotic resistance, Remodel focuses on reshaping the immune microenvironment to clear pathogens, and Repair emphasizes the restoration of the gastric mucosa and protection of the gut microbiota. We discuss the potential of biomaterials, including nanoparticles for targeted drug delivery and ROS generation, hydrogels for sustained release and mucosal repair, microspheres for enhanced drug loading and controlled release, and probiotics for microbiota restoration. Additionally, multimodal therapies such as phototherapy, sonodynamic therapy, and magnetic hyperthermia provide non-invasive, targeted treatments. These innovations align with HIM principles, integrating pathogen eradication with mucosal healing and microbiome protection. Future research should focus on optimizing these materials and validating their clinical applicability to improve patient outcomes and combat antibiotic resistance.